2013
DOI: 10.1111/epi.12331
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia for pediatric refractory status epilepticus

Abstract: SUMMARY Purpose Refractory status epilepticus (RSE) is a life-threatening emergency, demonstrating, by definition, significant pharmacoresistance. We describe five cases of pediatric RSE treated with mild hypothermia. Methods Retrospective chart review was performed of records of children who received hypothermia for RSE at two tertiary-care pediatric hospitals between 2009 and 2012. Key Findings Five children with RSE received mild hypothermia (32–35°C). Hypothermia reduced seizure burden during and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 59 publications
0
53
0
Order By: Relevance
“…In 2008, Corry et al [17] first reported the use of mild hypothermia treatment in patients with RSE and the results showed that hypothermia inhibited epileptic seizures. Then in 2013, Guilliams et al [18] also found that hypothermia exhibited obvious therapeutic effects on RSE. In 2014, Orbach et al [19] conducted a retrospective study on 224 cases of neonatal hypoxic-ischemic encephalopathy, and they found that low temperatures had an antiseizure effect.…”
Section: Historical Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2008, Corry et al [17] first reported the use of mild hypothermia treatment in patients with RSE and the results showed that hypothermia inhibited epileptic seizures. Then in 2013, Guilliams et al [18] also found that hypothermia exhibited obvious therapeutic effects on RSE. In 2014, Orbach et al [19] conducted a retrospective study on 224 cases of neonatal hypoxic-ischemic encephalopathy, and they found that low temperatures had an antiseizure effect.…”
Section: Historical Evolutionmentioning
confidence: 99%
“…These patients were subsequently under control after hypothermia treatment, and they experienced no further seizures after re-warming. In 2013, Guilliams et al [18] reported five cases of mild hypothermia treatment in patients with RSE. They found that an intravenous injection of antiepileptic drugs (midazolam/ phenobarbital/valproic acid/phenytoin) while receiving hypothermia (temperature reduced to 32~35 C, after reaching the target temperature within 3-48 h) effectively controlled seizures and maintained EEGs in a suppressive state.…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar model, deep hypothermia (20˚C) suppressed SE in 40% of rats (Kowski et al 2012). In a large pediatric case series that used mild hypothermia to treat refractory SE, it was found that hypothermia decreased seizure burden during and after pediatric refractory SE and may prevent refractory SE relapse (Guilliams et al 2013). However, it remains an experimental technique.…”
Section: Treatmentmentioning
confidence: 99%
“…Several clinical studies have demonstrated the utility of systemic cooling as an adjunct for the treatment of intractable epilepsy (Vastola et al, 1969;Sourek and Travnicek, 1970;Corry et al, 2008;Guilliams et al, 2013). We first investigated the effect of focal brain cooling on seizures after initial observations that the intraoperative irrigation of exposed cortex with iced saline (4°C) reduced or abolished the interictal activity.…”
Section: Introductionmentioning
confidence: 99%